Molecular Tools for Diagnosis of Pediatric Infectious Diseases - Nivedhana Subburaju (Pediatric Infectious Disease)
Molecular techniques constitute valuable tools to improve the diagnosis of bacterial infections in children when cultures remain negative, etiologies of which would otherwise go nondocumented. The clinical utility of such tests could be optimized by systematic prescription by the pediatricians after consulting the microbiologist.